ANALYSIS OF STUDENT’S CRITICAL THINKING ABILITY IN SOLVING SOCIAL ARITHMETIC PROBLEMS IN VIEW OF GENDER - Annisa Nur Aini Oktaviasari; Rita Pramujiyanti Khotimah (Prima: Jurnal Pendidikan Matematika, 2023)
This study aims to develop students' ability to use critical thinking to solve social arithmetic problems. This study adopted qualitative and descriptive methods. The subjects of this study included 3 male students and 3 female students from VII E of SMP Negeri 1 Masaran. The data collection techniques used in this study are tests, interviews and documents. Data validity is based on a triangulation process. Analytical techniques reduce data, display it, and draw conclusions. The results revealed differences in critical thinking skills when solving social computing tasks associated with gender differences. In terms of high critical thinking skills, both male and female students mastered all the indicators of critical thinking, namely interpretation, analysis, evaluation and reasoning. In terms of critical thinking ability, boys in the middle category can master three indicators, namely interpretation, evaluation and conclusion. Female students, on the other hand, can only understand explanatory, analytical and evaluative indicators. In the low category, critical thinking ability has only two indicators of critical thinking, interpretation and analysis.Keywords: critical thinking, gender, social arithmetic